The psychological content of “self-sacrificingness” and its level in conscripts - Irina М. Kyshtymova; Irina S. Shakhova (Rossijskij psihologičeskij žurnal., 2018)
This article touches upon the psychological status of the concept of “selfsacrificingness” and demonstrates its importance for the efficiency of the soldier. The features of the transformation of the ordinary semantics of “self-sacrificingness” are connected with the reduction of transcendental connotations and strengthening of humanistic ones. There is a lack of psychological reflection of the content of qualities of soldiers, which are required in service regulations and described in scientific studies as conditions of their willingness to implement the duty to defend the Fatherland. The authors (a) carried out the comparative analysis of the concepts of “self-sacrificingness” and “altruism”, (b) revealed the incompleteness of the concept of “altruism” to designate the readiness for a sacrificial act, (c) demonstrated the interrelation of self-sacrificingness with the level of sense development of the person, and (d) adduced the results of the empirical study of the sense development of conscripts and their willingness for sacrificial behavior. The study was carried out according to a multiparadigm logic, with the use of propositions of cultural-historical, existential, and psychosemiotic approaches. The study involved 45 conscripts. The authors developed a questionnaire for the diagnosis of the willingness for sacrificial behavior. To determine the level of sense development they used diagnostic indices of “object-centrism” and “sense 2”, techniques of psychosemiotic analysis of essays on any topic, as well as the index of decentration of the “Technique of Ultimate Senses”. The paper presents the analysis of the revealed correlations of the obtained scores of diagnostic indices. The results of the study demonstrated a direct correlation between self-sacrificingness and religion, everyday forms of helping behavior, as well as the level of sense development of the respondents; there was a reverse correlation with the index of self-esteem. The present study showed the importance of modeling and implementation of developing programs for conscripts, aimed at the development of the system of personal senses that can compensate for the sense insufficiency of the modern educational environment and contribute to their willingness to perform military duty.